Case Report: Endovascular technique for intravascular foreign body retrieval in severely preterm neonate [version 1; peer review: 2 approved] - Irhamni Irhamni; Terawan Agus Putranto; Taufiq Fredrik Pasiak; Listyo Julia; Marsha Ruthy Darmawan; Djuwita Adi Wahyono (F1000Research)
Background Intravascular foreign bodies (IFB) in severely preterm neonates present critical clinical challenges. Traditional surgical removals are often risky and may not be feasible in these patients. This case report aims to detail a successful endovascular approach for IFB retrieval in a severely preterm neonate. Case This is a case report of a 14-day old, male 30-week gestation neonate with a retained umbilical catheter fragment. The baby was referred after an unsuccessful explorative laparotomy by a paediatric surgery team. The endovascular procedure was performed using a 4 French (Fr) vertebra catheter and a One Snare wire in the right femoral region under low-dose fluoroscopy. The IFB was successfully removed. Post-procedure, the patient’s leukocyte count normalized, and he transitioned from ventilator support to a nasal cannula and eventually to room air within three days. The neonate could also tolerate oral intake, signalling a rapid recovery and low morbidity. Conclusions This case report highlights the potential of endovascular approaches for IFB retrieval as viable alternatives to traditional surgeries, especially in neonates where surgical options are limited or have failed. Further research is needed to standardize such minimally invasive techniques in neonatal care.